Measurement of partial branching fractions of inclusive charmless B meson decays to K+, K0, and π+ - Amo Sanchez, Pablo del; Adametz, A.; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We present measurements of partial branching fractions of B→K+X, B→K0X, and B→π+X, where X denotes any accessible final state above the endpoint for B decays to charmed mesons, specifically for momenta of the candidate hadron greater than 2.34 (2.36) GeV for kaons (pions) in the B rest frame. These measurements are sensitive to potential new-physics particles which could enter the b→s(d) loop transitions. The analysis is performed on a data sample consisting of 383×106B¯¯¯B pairs collected with the BABAR detector at the PEP-II e+e− asymmetric energy collider. We observe the inclusive B→π+X process, and we set upper limits for B→K+X and B→K0X. Our results for these inclusive branching fractions are consistent with those of known exclusive modes, and exclude large enhancements due to sources of new physics.
*The Babar Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 429 weitere Personen]
Gesehen am 04.10.2022
Im Titel ist das Zeichen + und die Zahl 0 hochgestellt